CF-LIBS quantification and depth profile analysis of Be coating mixed layers. (June 2021) - Dwivedi, V.; Marín-Roldán, A.; Karhunen, J.; Paris, P.; Jõgi, I.; Porosnicu, C.; Lungu, C.P.; van der Meiden, H.; Hakola, A.; Veis, P.
Highlights: LIBS & SIMS depth profiles analysis of Be-based layers containing C, O, H, & D-fuel. Deconvolution of Dα and Hα lines by Lorentz fitting for the quantification of D & H. MESB plot and Stark broadening of Hα line for the evaluation of T e and n e, resp. Determination of the fuel content by CF-LIBS and comparison with TOF-ERDA and IBA. Study of the variation of the elemental composition when changing T e and n e . Abstract: A remote LIBS system is being considered as an analysis tool in ITER for monitoring the erosion and fuel retention in the first wall. This necessitates further investigation of the performance of LIBS for thick co-deposited layers consisting of ITER-relevant materials. The main goal of this work is determining the fuel content of the samples and D depth profile by LIBS and to compare the results with those obtained by other methods. The studied samples were Be-based mixed coatings on W substrates, containing D and in some cases C, O, or both. These impurities are relevant not only for ITER, but also for other fusion devices, such as JET-ILW. The laser ablation was performed at 10 mbar Ar pressure using a 5 ns pulse Nd:YAG laser at 1064 nm. Suitable Be and Ar spectral lines were employed for the evaluation of the electron temperature of the plasma using multi-elemental Saha-Boltzmann (MESB) plots. The electron density was obtained from the Stark broadening of the Dα and Hα spectral lines following deconvolution. The average elemental content of each coating was then obtained by calibration-free LIBS (CF-LIBS) and are in agreement with other techniques (TOF–ERDA, IBA).